Penerapan Metode Bercerita dalam Membentuk Karakter Religius pada Anak Usia Dini di PAUD 17 Ramadhan, Kota Tangerang - Sadam Hidayahtullah Al-Amyan; Dadan Darmawan; Herlina Siregar (MASALIQ, 2025)
The formation of religious character in early childhood is a fundamental aspect of education, serving as the primary foundation for children's future moral, social, and spiritual development. One effective method for instilling religious values is storytelling, which conveys educational messages through an engaging and easily understood approach. This study aims to examine the implementation of the storytelling method in shaping the religious character of early childhood learners and to analyze its effectiveness, with a focus on PAUD 17 Ramadhan in Cibodas District, Tangerang City. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings indicate that teachers carried out thorough preparations in both content and technique, including the selection of relevant and varied stories, the use of supporting media such as finger puppets, and creative storytelling delivery through voice modulation, expression, and character imitation. The success of the storytelling method is reflected in the emerging religious habits of the children, such as praying before and after activities, maintaining cleanliness, showing politeness, and becoming familiar with prophetic stories and short surahs. The study concludes that storytelling is an effective method for developing religious character in early childhood when applied consistently and creatively, accompanied by habituation and teacher role modeling as the central figure in the educational process.